Revitalisasi Nilai Kewarganegaraan untuk Penguatan Tata Kelola Partisipatif di Kota Surakarta: (Sebuah Kajian Pustaka) - Abdulloh Isa Al Muhandis; Muhammad Al Farid; Wirda Wirda (Badan Riset dan Inovasi Daerah Kota Surakarta, 2026)
This study aims to analyze efforts to revitalize civic values in strengthening participatory governance in Surakarta City through a literature review approach. The main focus of this study is to examine how civic education can play a strategic role in fostering legal awareness, increasing community participation, and reinforcing democratic values at the local level. The results of the review indicate that revitalizing civic values is an essential foundation for building an empowered society that is critical and actively participates in governmental processes. Civic education that is adaptive to social and digital developments has proven effective in enhancing citizens’ legal and political literacy. In addition, collaboration between local governments, educational institutions, and civil society becomes a key factor in achieving inclusive and transparent governance. This study emphasizes that strengthening participatory governance requires not only formal policies but also a sustainable transformation of civic values as part of citizen character development. Thus, the revitalization of civic values in Surakarta is a strategic step towards realizing democratic, responsive, and socially just governance.